Antioxidant Activity, Mineral Absorptivity and Chemical Analysis of P. Graveolens - Kazheen H. Jawzal; Lina Y. Mohammed; Shinwar A. Idrees (مجلة بغداد للعلوم)
This article focuses on Pelargonium graveolens, a fragrant medicinal plant from the Geraniaceae family. The study examines the plant's phytochemical composition, antioxidant activity, and mineral absorptivity, with the plant being grown indoors. The study also examined the plant's ash content and antioxidant activity using a variety of techniques, and the results demonstrated that P. graveolens is effective at absorbing lead. The plant contains eight different minerals, including Cu, Mn, Co, Ni, Pb, Mg, Fe, and Ca. Statistical analysis was used to determine the level of antioxidants present, using DPPH, reducing power, and total antioxidant capacity methods. The extraction process used a mixture of water, 70% ethanol and absolute ethanol solvents in varying ratios. To conclude, the study examines Pelargonium graveolens, a fragrant medicinal plant, for its antioxidant activity and mineral absorptivity.